Folate Deficiency Increased Lipid Accumulation and Leptin Production of Adipocytes - Chan, Chun-Wai; Chan, Pei-Hsuan; Lin, Bi-Fong (Frontiers in Nutrition, 2022)
Imbalanced dietary habits are closely associated with poor micronutrients status and development of obesity. Previous studies have shown that serum folate level is decreased in obese individuals. However, whether folate deficiency could result in adiposity is still unclear. The aim of this study was to investigate the effects of dietary folate on lipid accumulation and leptin production using both in vivo and in vitro studies. Male C57BL/6 mice were fed with a diet with (f1) or without folate (f0) in a high-fat (HF) diet containing high-sucrose (HFS-f1, HFS-f0) for 4.5~5 months in the Experiment 1, or a HF diet (HF-f1, HF-f0) for 12 months in the Experiment 2, or a HF diet containing high-fructose (HFF-f1, HFF-f0) for 12 months in the Experiment 3, compared with the normal-fat (NF-f1, NF-f0) diet, respectively. Serum levels of folate and leptin, white adipose tissue (WAT), size of adipocytes, hepatic contents of triglyceride (TG) and cholesterol were measured. In vitro study, TG contents, proinflammatory cytokines, leptin, and expressions of hypoxia-inducible factor (HIF)-1α and lipogenesis-related genes of 3T3-L1 adipocytes cultured with (f1) or without (f0) folate were assayed. The results showed that folate deficiency together with high-fat diet (HFS-f0, HF-f0, HFF-f0) had higher WAT mass, adipocyte size, serum leptin level and hepatic TG compared to those of the folate-sufficient groups (HFS-f1, HF-f1 and HFF-f1). Folate deficiency with high-fat high-sucrose or -fructose diet (HFS-f0, HFF-f0) significantly increased body weight of the mice. Increased intracellular TG, leptin, monocyte chemotactic protein (MCP)-1 and interleukin (IL)-6 levels, and the expression of Hif1α and lipogenesis-related genes Cebpα, Cebpβ, Acc1, Fasn and Fabp4 were also detected in folate-deficient 3T3-L1 adipocytes. Our results suggested that folate deficiency increased lipid accumulation and leptin production of adipocytes, and thus inadequate folate status might be one of the risk factors of adiposity.